ChemInform Abstract: A Strategy for the Preparation of Thioantimonates Based on the Concept of Weak Acids and Corresponding Strong Bases. Issue 15 (April 2015) - Anderer, Carolin; Delwa de Alarcon, Natalie; Naether, Christian; Bensch, Wolfgang
Abstract The layered compounds (III) and (V) are synthesized by a new hydrothermal synthetic approach which is based on the in situ formation of a basic medium by the reaction between the strong base SbS43‐ and the weak acid H2O.